Psychological interventions that target sleep reduce pain catastrophizing in knee osteoarthritis. Issue 11 (November 2017) - Lerman, Sheera F.; Finan, Patrick H.; Smith, Michael T.; Haythornthwaite, Jennifer A.
Abstract : Abstract: Pain catastrophizing is a significant risk factor for patients with knee osteoarthritis (KOA) and thus is a target for many psychological interventions for pain. This study examined if interventions targeting sleep found to be effective in improving sleep in KOA also reduce pain catastrophizing measured as a trait through the pain catastrophizing scale and measured as a daytime and nocturnal state through daily diaries. Secondary analyses were conducted on data collected as part of a randomized controlled trial assessing the effectiveness of cognitive behavioral therapy for insomnia in patients with KOA at 5 different time points: pretreatment, midtreatment and posttreatment and at 3- and 6-month follow-up. One hundred patients diagnosed with KOA and insomnia were randomized to receive either 8 sessions of cognitive behavioral therapy for insomnia or a placebo intervention of behavioral desensitization. Multilevel modeling revealed that both intervention groups showed a significant reduction pretreatment to posttreatment in all 3 measures of pain catastrophizing and maintained stable levels through the 6-month follow-up. Increased sleep continuity early in treatment (pretreatment to midtreatment), but not reductions in pain, was associated with a reduction in trait and nocturnal catastrophizing later in treatment (midtreatment to posttreatment). These results suggest that short interventions focusing on sleep can significantly reduce pain catastrophizing even in a clinical population with low baseline levels of catastrophizing, possibly through improving sleep continuity. Abstract : Pain catastrophizing measured as a trait and as a daytime and nocturnal state can be significantly reduced through interventions targeting sleep in patients with knee osteoarthritis.